Respuesta :

srlt2

Answer:

3rd option is correct

Step-by-step explanation:

:)

The vertex form of the equation is [tex]f(x) = (x+1/2)^2 + 3/4[/tex]

Vertex form of an equation

Given the expression [tex]f(x) = x^2 + x +1[/tex]

The vertex form is expressed as shown below:

[tex]f(x) = x^2 + x +1\\f(x) = x^2 + x + 1^2 +1 - 1^2\\f(x) = (x+1)^2 - 0[/tex]

Express the result in vertex form.

[tex]f(x) = (x+1/2)^2 + 3/4[/tex]

Hence the vertex form of the equation is [tex]f(x) = (x+1/2)^2 + 3/4[/tex]

Learn more on vertex form here: https://brainly.com/question/525947

ACCESS MORE